Konsep Pendidikan Khuluqiyah dalam Prespektif Kitab Washoya Al Abaa’ Lil Abna’ untuk Menanggapi Pendidikan Era Industri 4.0 - Bahroin Budiya (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2020)
This study aims to deepen moral knowledge in the book washoya al-abaa 'lil abna' by Sheikh Muhammad Syakir, this type of research is library research, data collection models using interactive methods by gathering primary and secondary sources before performing data presentation. The results of this study that the book washoya al-abaa 'lil abna' by Sheikh Muhammad Syakir enlighten us about moral values that are classified into 4 parts, including: morals to God, morals to fellow human beings, morals to oneself and children in morality procedures, apart from that this book has the concept of moral education that can guide as well as strengthen the morale of students in educational era 4.0.